Allometric relationships of Donax sp. collected from Sungai Janggut: ecological insights, environmental stress, and coastal conservation implications - Irina Erliana; Azzarizal Al-Azri Saipul Bahri; Danish Shamer Shamsir; Nur Qistina‘Aisyah Md Sadakah; Ameerul Syahmi Che Rozilan; Rima Amira Nordin; Ezita Qaisara Ridzuan; Khairiah Jasmi; Amalia Khadeija Sorfeena Zaidi; Norsyakila Mohd Radzuan; Kavelashini Navarathnaraja; Rabiatul Adawiyah Nor Hisham; et al. (MedCrave Group, 2024)
This study investigates the allometric relationships between shell length, width, height, and weight of Donax sp. collected from Sungai Janggut, (on 7 May, 2024), Malaysia, across three groups (Group 1: N=429; Group 2: N=342; Group 3: N=329; Group All: N=1100). Pearson’s correlation analysis revealed significant differences among the groups, with Group 3 displaying strong positive correlations among allometric parameters, particularly between shell length, width, and weight, indicating optimal growth conditions. Conversely, Groups 1 and 2 exhibited weaker correlations, suggesting growth disruptions likely due to environmental stressors or suboptimal habitat conditions. Factor analysis further confirmed these patterns, with shell length and width as primary contributors to shell weight, while shell height showed negative or minimal influence. Multiple regression analysis identified shell length as the dominant predictor of shell weight, particularly in Group 3, followed by shell width, while height contributed negatively in most groups. The results provide ecological insights into the adaptive strategies of Donax sp. under varying environmental pressures and highlight their role as bioindicators of ecosystem health. From a coastal conservation perspective, these findings underscore the need to protect intertidal habitats to sustain Donax sp. populations and the essential ecosystem services they provide.